Clinical Evaluation of Helical Rim Reconstruction Using a Unipedicle Flap: Benefits and Outcomes - HamaRashid, Hunar; Hassan, Jalal Ali (Journal of Sulaimani Medical College, 2025)
Background: Helical rim deformities of the auricle, resulting from trauma, burns, congenital malformations, or oncological resections, pose significant reconstructive challenges. The unipedicular flap has emerged as an effective technique, offering vascular reliability, aesthetic congruity, and minimal donor site morbidity. Objective: This study aims to evaluate the efficacy of helical rim reconstruction using the unipedicular flap in terms of aesthetic, functional, and psychological outcomes. Patients and Methods: A randomized trial was conducted from February 1 to June 1, 2025, at Sulaimani Hospital and a private clinic, involving 14 adult patients with helical rim defects. Patients were selected based on inclusion criteria, including the ability to undergo surgery without general anesthesia and consent to participate. Surgical outcomes, aesthetic results, functional recovery, and satisfaction were assessed, with standardized procedures. Follow-up occurred at 1 month. Results: The study included 14 patients (mean age 32.71 ± 10.07 years; 71.4% female, 28.6% male). Smoking status: 50% never smokers, 21.4% current smokers, 28.6% former smokers. Most (92.9%) underwent superiorly based local flap reconstruction, with 64.3% having defects of 2–3 cm. Satisfaction: 57.1% "satisfied" with appearance, 50% "very satisfied" with symmetry, and 57.1% "very satisfied" with helical rim contour. Flap take rate was 92.9%, with 13 patients achieving 75-99% flap take, and 7.9% developed epidermal necrosis. All patients were "very satisfied" with comfort wearing eyeglasses. Scar visibility was "neutral" for 50%, and 78.6% were "very satisfied" with donor site appearance. Conclusion: Unipedicular flap helical rim reconstruction offers excellent outcomes, high satisfaction, and minimal complications, with a single-stage approach
Keywords: Aesthetic outcomes; functional recovery; helical rim reconstruction; unipedicular flap